A community based study on breast feeding practices in Gampaha district - A. Jayatilleka; D. N. Femando (College of Community Physicians of Sri Lanka, 2002)
Objective: To determine the prevalence of exclusive breast feeding, the predominant breast feeding rate and the bottle feeding rate, and to identify the factors influencing exclusive breast feeding in the Gampaha district.   Methodology: A sample of 1075 mothers, each with a child aged less than 365 days was identified from two randomly selected Medical Officer of Health areas, Information related to birth and feeding practices were obtained using an interviewer-administered structured questionnaire. Mothers' knowledge on breastfeeding was also assessed.   Results: Initiation of breast feeding was universal, with an exclusive breast feeding rate (EBF)of 63.7%. Logistic regression analysis identified that 'mother working outside the home', delivery being not a normal delivery, not receiving antenatal education and poor knowledge on EBF were negatively associated with EBF.   Conclusions: Even though an improvement in the EBF rate is seen over the past years, there is a need to strengthen antenatal and post-natal practices to encourage EBF and to develop innovative strategies to promote EBF among working women.